PENGARUH MEDIA GAMBAR TERHADAP HASIL BELAJAR SISWA PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SD - Septiawan Lumban Gaol; Saut Mahulae; Darinda Sofia Tanjung (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This research was conducted at the Dharma Wanita Pertiwi Private Elementary School, Medan Selayang District and the research was focused on fourth grade students. The purpose of this study was to determine the effect of media images on student learning outcomes on the theme The Beauty of Diversity in My Country, Grade IV. This research is motivated by the low student learning outcomes and also student interest in learning when teaching and learning activities take place. The research approach used is a quantitative approach with analytic descriptive method. The design used in this research is the one-group pretest-posttest design. The population used was class IV, with a sample of all fourth grade students at SD Dharma Wanita Pertiwi Private Elementary School. Based on the results of the study, the correlation coefficient value of R count 0.719> R table 0.396 means that there is a strong influence between media images on student learning outcomes. From the results of the t-test conducted, it can be concluded that there is an influence between media images on student learning outcomes of SD Dharma Wanita Pertiwi Private Elementary School.